The Comparative Ecology of the Brown Hyaena (Hyaena brunnea) in Makgadikgadi National Park and a Neighbouring Community Cattle Area in Botswana - Du Toit, J.T. (University of Pretoria, 2013)
Dissertation (MSc (Zoology))--University of Pretoria, 2007.